Management problems and desired interventions in the private sector in Bhutan - Kharka, Damber Singh (1999)
An attempt is made to study the experiences of entrepreneurs and managers in the private sector in Bhutan with regards to business trends, market knowledge, ways of assessing market and business performance. This has provided an insight into current business practices in Bhutan. The paper also reveals entrepreneurs' perceptions of factors that lead to business success and the problems/barriers faced by the private sector. Weighing the current and desired business practices, the paper has identified the need for development of management system and management training, especially in the basic areas of accounting, marketing, finance and personnel management. - Reproduced
Keywords: Management - Bhutan; Private sector - Bhutan; Management